أثر كفاءة نظم المعلومات في اتخاذ القرارات دراسة قياسية ميدانية لمجمع صيدال خلال فترة 2015-2016 - عيشوش, محمد الحافظ (University of eloued - جامعة الوادي, 2018)
تناول البحث الحالي موضوع نظام المعلومات الإدارية ومعرفة مدى تأثيره على صناعة القرارات في المنظمة، من خلال تحليل علاقة الارتباط والأثر بين متغيرات الدراسة وذلك من خلال دراسة آراء عينة من المسؤولين الإداريين في مجمع صيدال، وقد تم معالجة مشكلة بحثية رئيسية مفادها أن غياب المعلومات يعرض الإدارة أو صانعي القرارات إلى اتخاذ قرارات غير رشيدة تؤثر بدورها على نجاح المنظمة. وقد تم اعتماد استمارة الاستبيان كأداة رئيسية في جمع البيانات والمعلومات للجانب الميداني للبحث من خلال توزيع الاستمارة على الأفراد ذوي العلاقة بالموضوع وتم استخدام التحليل الإحصائي لاختبار فرضيات الدراسة ومعالجة البيانات وقد تم التوصل إلى مجموعة من النتائج، حيث بينت الدراسة أن توجد علاقة ارتباط لنظام المعلومات بالإدارة من أجل زيادة قدرة المدراء على صناعة القرارات واستقراء المستقبل ومواجهة تحديات البيئة الداخلية والخارجية للمنظمة. وقد تضمن البحث عدة توصيات من أهمها ضرورة وضع نظام فعال للاتصالات الداخلية بحيث يمكن الإدارات من الاتصال مع بعضها البعض وبشكل يساهم في جمع البيانات وتحليلها، وصولا لصنع القرارات .اضافة الى ضرورة خلق قاعدة موحدة للبيانات والمعلومات تساهم بفعالية في تزويد صانعي القرارات بالبيانات والمعلومات الدقيقة. The present study tackled the issue of information systems and its impact on the decision-making process in the organization by analyzing the relationship of correlation and impact between the variables of the study by studying the opinions of a sample of the administrative officials at the SAIDAL group. Or decision-makers to make irrational decisions that, in turn, affect the success of the Organization. The questionnaire was used as the main tool in collecting data and information for the field side of the research through the distribution of the questionnaire to the relevant individuals. The statistical analysis was used to test the hypotheses of the study and data processing. Several results were obtained. To increase the ability of managers to make decisions and extrapolate the future and meet the challenges of the internal environment and external to the Organization. The study included several recommendations, the most important of which is the need to establish an effective internal communications system so that departments can communicate with each other in a way that contributes to data collection and analysis, to decision making. In addition, it is necessary to create a unified data and information base that will effectively provide decision makers with accurate data and information.
مقال
Keywords: المخاطر المصرفية، العائد والمخاطرة، عائد على رأس المال المعدل بالمخاطر نموذج RAROC ، مصرف الشرق الأوسط العراقي. banking risk, return and risk, risk weighted capital (RAROC model), Middle East Iraqi.